THE KYIV PERIOD OF MIKHAIL MORDKIN’S CREATIVITY (1918-1919) - Danyliuk, Uliana (Scientific Journal of Polonia University, 2022)
The purpose of the study is to identify the main directions of Mikhail Mordkin’s creativity in Kyiv in 1918-1919. Chronological, comparative, typological and other methods are used in this work. The Kyiv period of M. Mordkin’s creativity is associated with his pedagogical, performing and choreographic activities. His productions of the ballets Flowers of Granada, Giselle, La Fille mal gardée (The Wayward Daughter), as well as dance numbers and divertissements in opera and drama performances became meaningful to the artistic life of the city. M. Mordkin gained valuable experience of the director as a result of cooperation with Ukrainian creative intellectuals (L. Kurbas, M. Bonch-Tomashevsky, A. Petritsky, V. Verkhovinets). The stage production skills of Mordkin as the dancer served as an example for many Ukrainian artists. Mordkin as the teacher managed to significantly increase the size of the ballet troupe of the Kyiv Opera in a short time. It was made thanks students from his own studio, he expanded their professional capabilities through careful and systematic physical training. The research materials can serve as a basis for creating special courses on the history of choreography, can be used in subsequent theoretical studies devoted to the learning of Russian and Ukrainian ballet theaters or in the educational process in academic institutions of the corresponding profile.